Nanoscale, automated, high throughput synthesis and screening for the accelerated discovery of protein modifiers. Issue 5 (5th May 2021) - Gao, Kai; Shaabani, Shabnam; Xu, Ruixue; Zarganes-Tzitzikas, Tryfon; Gao, Li; Ahmadianmoghaddam, Maryam; Groves, Matthew R.; Dömling, Alexander
Abstract : Acoustic dispensing was used to synthesize 1536 compounds on a nano scale, screened by differential scanning fluorimetry, cross-validated by microscale thermophoresis against the protein interaction menin–MLL to discover binders, one co-crystallized. Abstract : Hit finding in early drug discovery is often based on high throughput screening (HTS) of existing and historical compound libraries, which can limit chemical diversity, is time-consuming, very costly, and environmentally not sustainable. On-the-fly compound synthesis and in situ screening in a highly miniaturized and automated format has the potential to greatly reduce the medicinal chemistry environmental footprint. Here, we used acoustic dispensing technology to synthesize a library in a 1536 well format based on the Groebcke–Blackburn–Bienaymé reaction (GBB-3CR) on a nanomole scale. The unpurified library was screened by differential scanning fluorimetry (DSF) and cross-validated using microscale thermophoresis (MST) against the oncogenic protein–protein interaction menin–MLL. Several GBB reaction products were found as μM menin binder, and the structural basis of the interactions with menin was elucidated by co-crystal structure analysis. Miniaturization and automation of the organic synthesis and screening process can lead to an acceleration in the early drug discovery process, which is an alternative to classical HTS and a step towards the paradigm of continuous manufacturing.